THE AVAILABILITY ANALYSIS OF 21ST CENTURY SKILL INDICATORS ON PHYSICS WORKSHEET OF SENIOR HIGH SCHOOL GRADE X SEMESTER 1 IN PASAMAN DISTRICTS - Putri Diana; Umi Isriyah; Wahyuni Satria Dewi; Akmam Akmam; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2021)
Worksheets that can help students develop 21st century skills are worksheets that contain indicators of 21st  century skills. Based on the results of preliminary observations made in the field, the student worksheets used by schools in Pasaman District still vary. It is not known whether these various worksheets include indicators of 21st  century skills. Therefore, a study was conducted with the aim of analyzing the 21st  century skill indicator in physics worksheets grade X Semester 1 in Pasaman District.This type of research is a descriptive study with a qualitative approach. The population in this study were all Physics Worksheets grade X Semester 1 used by 12 public Senior High School in Pasaman Districts. Furthermore, for the school sampling technique using purposive sampling technique with schools selected by high category schools, medium category schools and low category schools based on the results of the 2019 National Examination of the total high school population in Pasaman Regency. Meanwhile, the sample of student worksheets in this study used a total sampling technique. The sample of worksheet in this study were 2 worksheet published by publishers which were used the most by schools in Pasaman district, and 3 worksheet made by physics subject teachers. Based on the results of the study, it is concluded that the 21st century skill indicator with the highest 37% is in the LKS Intan Pariwara by Risdiyani Chasanah and friends. Meanwhile, and friends with a proportion of 12% in the category of not facilitating.